Neo-Nationalism: A Tool for National Integrity - Aryal, Manish (Unity Journal, 2021)
An ever-growing trend of radical rightist parties has brought newer dynamics to world politics. Neo-nationalism has further substantiated national integrity for changing the socio-cultural, economic and political landscape brought by globalization during the 1980s. The paper intends to analyze the concept of neo-nationalism. The paper explores this concept through an intensive study of the origin and background of neonationalism. In the paper, a study is conducted on the use of national integrity and patriotism to implement the concept of neo-nationalism in those countries. The major precautions in adopting the neo-nationalism concept are discussed in the project. A deep study is undertaken to investigate reasons that have led the world on a modern neo-nationalist order are discussed. Four peculiar reasons, in particular, the oil crisis, the collapse of the USSR and 9/11, financial and refugee crisis, and new nationalists focusing on national integrity have remained key contributors to the formation of the neo-nationalist society in the modern world. The paper studies all the reasons in depth and analyzes the key factors which might determine the new world order. The paper also uses two contemporary examples of Scotland and Western Europe to study the effects of neo-nationalism. A proper comprehensive study is done to recognize the concept of neo-nationalism and its effect on societies. The positive and negative effects are expanded to formulate a better cohesive study. Neo-nationalism is found to be a double-edged sword with monumental benefits and drawbacks. Its concept must be adopted with proper care and precaution so that major extremity groups wouldn’t be formulated.